(untitled) (International Journal of Engineering and Computer Science, 2015)
Cloud computing is emerging as a new paradigm for next generation computing in the field of computer science and information technology because of their attractive services such as adaptive, online, value added and pay as use scheme. Virtualization is the core technology in the cloud computing, which allow the sharing of physical resources. With the help of virtualization single physical device can be share by the multiple users. So it increased the resource utilization. Cloud is a very large in size and having complex structure. Cloud resources are heterogeneous and geographically distributed and the resource demanded by the user may change dynamically on runtime. So the resource management and the resource scheduling in such a large-scale distributed environment is a very challenging task. In cloud environment each data center can contain number of host, so there may be a situation when some hosts are overloaded and some are underloaded. To avoid this situation we proposed a double threshold based load balancing approach, where threshold is decided based on the utilization. This approach motivated by the fact that overloaded situation can’t be avoided, but can be control by assigning the dynamic threshold. For assigning the dynamic threshold we monitored host utilization for each 20 Second and assign the threshold based on the utilization in the previous interval. Experiment result shows that our approaches reduce the energy consumption and minimize the number of migration